Peran Insulin-like Growth Factor-1 dan Adiponektin dalam Hubungan antara Asupan, Aktifitas Fisik, dan Sindrom Metabolik pada Anak dan Remaja Melayuaustronesia: Protokol Resensi Sistematis - Dudung Angkasa; Tyas Putri Utami; Budi Mulyana; Razali Mohamed Salleh; Hosni Hasan; Mahenderan Appukuty (Universitas Airlangga, 2024)
Background: Risk factors of metabolic syndromes develop in childhood and tacks across life, which may lead them to a higher risk of getting cardiovascular diseases and premature deaths. A healthy diet and being physically active are supposed to modify the risk of metabolic syndromes (MetS). However, those observations primarily work in adult samples and the biological mechanisms that link that behavioral factor and MetS in children and adolescents still need to be explored. Asian people are more likely to get MetS than their white counterparts, but study in Malay-Austronesia children is minimal. Objectives: This study aims to comprehensively review and appraise studies that elucidate biological factors (insulin-like growth factor-1 and adiponectin) that possibly mediate the relationship between those risk factors and MetS in Malay-Austronesia children. Methods: The search will be performed in PubMed, Scopus, Web of Science, Google Scholar, and local databases Garuda (Garba Rujukan Digital, Indonesian) and Mycite (Malaysian citation index). All prospective cohort studies that examine the association of one of the behavioral factors (dietary intakes OR physical activity) AND one of the biological factors (Insulin-like growth factor OR adiponectin) with MetS or its components in healthy children with the exposures start from the age of 1 and 12 years of age and outcomes begin from 1 year and two months until the age of 18 years old are eligible. Only literature in English and local languages from inception to 31 December 2023 that match eligibility criteria will be included. National Institute of Health tool for observational studies will be used to assess the quality of included studies. This work was registered to PROSPERO CRD42023471481. Results: The findings may shed light on how the predefined biological factors mediate those behavioural factors on MetS in children. The findings will also be published in a peer-reviewed journal. Conclusion: This review utilizes relevant databases to optimize the searching of eligible studies. Eligible studies will be extracted by more (four) researchers who work independently with a predefined data extraction template. There are possibility some studies report significant finding on IGF-1 binding protein instead of total IGF-1 or its molar ratio will challenge the statistical analysis.